BRICS in the Digital Age: Investigating Technological Innovation and Knowledge Sharing as Catalysts for Economic Transformation - Haryono, Haryono (Eastasouth Institute, 2024)
The digital age presents unparalleled opportunities for economic transformation, particularly for emerging economies like BRICS (Brazil, Russia, India, China, and South Africa). This study investigates the role of technological innovation and knowledge sharing as catalysts for economic development through a normative juridical analysis of legal frameworks. The findings reveal significant disparities in intellectual property laws, data governance policies, and innovation ecosystems among BRICS nations, hindering seamless collaboration. The study emphasizes the need for harmonized juridical mechanisms to address challenges such as digital inequality, cybersecurity threats, and geopolitical tensions. By proposing unified intellectual property agreements, standardized data governance policies, and joint R&D programs, the research offers actionable insights into fostering innovation and collaboration for sustainable economic transformation in the digital era.